CapViT: Cross-context capsule vision transformers for land cover classification with airborne multispectral LiDAR data - Yu, Yongtao; Jiang, Tao; Gao, Junyong; Guan, Haiyan; Li, Dilong; Gao, Shangbing; Tang, E; Wang, Wenhao; Tang, Peng; Li, Jonathan (International journal of applied earth observation and geoinformation, 2022)
•Capsule vision transformer formulation for entity-aware feature extraction.•Cross-context transformer encoders for high-quality feature embedding.•Dual-path multi-head self-attention modules for feature semantic promotion.•Cross-context capsule vision transformer for land cover classification. Equipped with multiple channels of laser scanners, multispectral light detection and ranging (MS-LiDAR) devices possess more advanced prospects in earth observation tasks compared with their single-band counterparts. It also opens up a potential-competitive solution to conducting land cover mapping with MS-LiDAR devices. In this paper, we develop a cross-context capsule vision transformer (CapViT) to serve for land cover classification with MS-LiDAR data. Specifically, the CapViT is structurized with three streams of capsule transformer encoders, which are stacked by capsule transformer (CapFormer) blocks, to exploit long-range global feature interactions at different context scales. These cross-context feature semantics are finally effectively fused to supervise accurate land cover type inferences. In addition, the CapFormer block parallels dual-path multi-head self-attention modules functioning to interpret both spatial token correlations and channel feature interdependencies, which favor significantly to the semantic promotion of feature encodings. Consequently, with the semantic-promoted feature encodings to boost the feature representation distinctiveness and quality, the land cover classification accuracy is effectively improved. The CapViT is elaborately testified on two MS-LiDAR datasets. Both quantitative assessments and comparative analyses demonstrate the competitive capability and advanced performance of the CapViT in tackling land cover classification issues.